AGK-2 protects the tymus aganist D-Galactose induced senescense in rats - BAHAR, ASLI NUR (My University, 2023)
INTRODUCTION-AIM: Immune aging with advancing age is associated with thymic involution, changes in B and T cellnumbers, increased oxidative stress and apoptosis, and decreased autophagy. D-Galactose (D-Gal) administration is a modelused in aging. SIRT2, a member of the sirtuin family, has been shown to increase with age and inhibit autophagy. In this study,we aimed to investigate the effects of AGK2, a SIRT2 inhibitor, on malondialdehyde (MDA) for oxidative stress, SIRT2expression, LC3 as autophagy parameter, apoptosis parameters Bax, Bcl2, Bax/Bcl2 ratio and thymic histological structure inthymus tissue.METHODS: A total of 24 young male (3 months old) Sprague Dawley rats were used. Rats were divided into 4 groups asControl, D-Gal, Solvent+D- Gal L, D-Gal +AGK2+Solvent. D-galactose (150 mg/kg/day), AGK-2 (10μM/bw) as specific SIRT2inhibitor, 4% DMSO+PBS as solvent and saline were administered subcutaneously to the experimental and control groups for10 weeks. MDA level in thymus tissue was measured by spectrophotometer, SIRT2, apoptosis and autophagy related proteinlevels were measured by western blot method. Thymus structure was evaluated by HE staining. Statistical analysis wasperformed by ANOVA (post hoc LSD) and Pearson correlation test (p<0.05). Data were presented as mean±SEM.RESULTS: D-galactose administration increased MDA levels and decreased LC3 protein expression in thymus tissue. D-Galadministration caused thymus atrophy and loss of cortico-medullary border. AGK-2 treatment decreased MDA level, Baxexpression, Bax/Bcl-2 ratio, significantly increased LC3 level and restored cortex-medulla border and cell structure in thymustissue. LC3 was positively correlated with Bcl-2 and negatively correlated with Bax and Bax/Bcl2 ratio.CONCLUSION: Our study showed that AGK-2 decreased lipid peroxidation, induced autophagy and suppressed apoptosis inD-Galactose-induced aging, and may protect the thymus from the negative effects of aging.ACKNOWLEDGEMENT: This work was supported by Gazi University Scientific Research Project Foundation (Project No: TTU-2021-7192)
Keywords: Sağlık Bilimleri; Temel Bilimler; Health Sciences; Natural Sciences; Klinik Tıp (MED); Temel Bilimler (SCI); Doğa Bilimleri Genel; ÇOK DİSİPLİNLİ BİLİMLER; Clinical Medicine (MED); Natural Sciences (SCI); NATURAL SCIENCES, GENERAL; MULTIDISCIPLINARY SCIENCES; Multidisipliner; Multidisciplinary